Resilience and perceived social support as predictors of emotional well-being - Murat YILDIRIM; Mehmet Emin TURAN; Najwa Salem ALBELADI; Pietro CRESCENZO; Amelia RIZZO; Gabriella NUCERA; Giuseppe FERRARI; Alla NAVOLOKINA; Lukasz SZARPAK; Francesco CHIRICO (Journal of Health and Social Sciences)
Introduction: Emotional well-being is a key ingredient of well-being and positive mental health. Resilience and perceived social support have been found to be important factors influencing emotional well-being. Age, gender, and personality traits have also been suggested as potential predictors of emotional well-being. However, it is unclear to what extent resilience and perceived social support predict emotional well-being after controlling for these variables among Saudi adults. Therefore, this study aims to examine the unique contribution of resilience and perceived social support in predicting emotional well-being while controlling for age, gender, and personality traits. Methods: The participants were young Saudi adults (83.64% females) whose ages ranged from 18 to 60 years, with a mean age of 32.37 (SD = 8.64). They completed an online survey comprising the Brief Resilience Scale, Multidimensional Scale of Perceived Social Support, Scales of Positive and Negative Experiences, Ten-Item Personality Inventory, and a socio-demographic questionnaire. Results: The results showed that after controlling for age, gender, and personality traits that showed an influence on emotional well-being, resilience and perceived social support exerted a statistically significant influence on the emotional well-being of international young adults by explaining a significant amount of unique variance. Discussion: The findings of this study provide important insights into the factors that contribute to emotional well-being among young Saudi adults. The findings suggest that the development of effective interventions and programs aimed at promoting emotional well-being among young Saudi adults should focus on enhancing resilience and perceived social support.